Vulnerability assessment of environment and natural resources in Vietnam coastal zone for sustainable use of natural resources, environment protection and adaptation to climate change (case study the Red River Delta coastal zone) - Nhuan, Mai Trong; Quy, Tran Dang; Hue, Nguyen Thi Hong; Dung, Luu Viet; Tuan, Hoang Van; Trang, Bui Thuy; Quyen, Pham Minh; Lua, Tran Thi; Que, Nguyen Ho; Nga, Le Thi; Linh, Nguyen Thuy; Thuy, Vu Thi Thu; et al. (VNU Journal of Science: Earth and Environmental Sciences; Vol 27 No 3, 2011)
Abstract. The Red River Delta Biosphere Reserve has the highest biodiversity in the Northern Vietnam, has an important role in protecting environment and natural resources and socio - economic development. In recent years, study area has been increased vulnerability by negative human activities (e.g., agriculture, aquaculture, transportation and industry) and climate change. Using ArcGIS 9.3 and Expert Choice 11 software, this article presents the results of vulnerability assessment map of environment and natural resources. Based on vulnerability assessment of environment and natural resources, several solutions aimed at sustainable use of natural resources, environmental protection, disaster prevention and mitigation, and adaptation to climate change have been proposed such as planning for sustainable use of environment and natural resources (eco-agriculture, eco-aquaculture and eco-tourism), environmental protection, raising awareness of community. Research results have significant roles particularly in establishing policies and strategies to protect natural resources and environment, mitigating hazards, adapting to climate change. Keywords : vulnerability assessment, sustainable use, climate change.